VR serious game to treat schizophrenia - Antunes, Alexandre Fernandes (2022)
The present work aims to optimize and produce scenarios of a serious game, and improve its immersiveness, enabling the capture of feedbacks, by configuring sensors that can monitor the user of the application for changes in the game in real time, making it possible to have better control over the player’s experience. With this, progressing research into the improvements of virtual reality when applied to the treatment of people with schizophrenia.